How to Improve Healthy Environment in Urban School Climate (USC) by Communication Language Strategies? Arabic Based Communication Language and Statistic Description Analysis - Fauziah, R. Siti Pupu; Kartakusumah, Berliana; Suherman, Irman; Roestamy, Martin; Martin, Abraham Yazdi; Monaya, Nova (Universitas Negeri Makassar, 2023)
The purpose of this research is to explain communication language factors to improve a healthy environment in an Urban School Climate (USC). This research also reviews the USC definition and why communication language is so important in improving a healthy environment in schools. The research method used was a mixed method with a sequential exploratory strategy approach, data collection was carried out by conducting interviews and distributing questionnaires via Google Forms to students in junior high schools, Bogor. Qualitative data analysis was carried out using the Miles and Huberman model and using of NVIVO 12 software, while quantitative data analysis was carried out using descriptive statistical analysis with the help of SPSS version 22.0. The research results show that communication language is important to improve a healthy environment in Urban School Climate (USC) which is described by 4 dimensions, namely 1) a safe environment, 2) teacher support, 3) individual social relationships and 4) family atmosphere. Arabic-based communication language styles, namely qaulan baligha, qaulan maysura, qaulan layyinan, qaulan ma'arufan and qaulan kariman can be used as communication language strategies to improve a healthy environment in schools. The impact of the results of this research is that teachers and students see the importance of using good communication language so that they are accustomed to using Arabic-based communication language styles to support the creation of a good USC characterized by a healthy environment.